Heavy Metals Bioaccumulation Pattern of Bivalve Geloina spp., and Crustaceans Penaeus marguensis and Scylla serrata from the Southern Central Java Ocean Margin, and Its Consumer's Safety - Sri Noegrohati (Indonesian Food and Nutrition Progress, 2005)
Aquatic organisms exposed to low lovel natural heavy metals pollutant tend to accumulate in their tissue by means of metabolic and biosorption processes. However, the influence of external environment to heavy metal bioavailability and internal organism characteristics to bioaccumulation processes remain uncertain. In this work, the influence of Cu, Zn, Cd and Hg bioavailability, feeding strategies and heavy metals homeostasis regulations or detoxification mechanisms to bioaccumulation pattern in aquatic bioindicators were studied.            Only Hg in Segara Anakan water samples was determined, while Cu, Zn and Cd were not detected. Sediment samples of Segara Anakan indicated higher heavy metals level than those of Serang river mouth, but only Hg concentration in sediment samples of Segara Anakan which is significantly higher than those of Serang river mouth, while Cd was not detected. The trend of heavy metals bioconcentration ratio of filter feeder Geloina spp and planktonic grazer Penaeus marguensis follows the desorption coefficient, i.e. Zn>Hg>Cu, but the bioconcentration trend in Scilla serrata, which is macrobenthos predator, is Hg>Zn>Cu.            The exposed Cu was not accumulated by Geloina spp., but accumulated at highest concentration in the exoskeleton of Penaeus marguensis and cartilage of Scilla serrata. Highest accumulation concentration of Zn and Hg were determined in meat, and lower concentrations were determined at other tissues. The extent of heavy metals bioaccumulation in Geloina spp. and Scilla serrata reflect the pollution of the surrounding environment, but the extent of heavy metal bioaccumulation in Penaeus marguensis were influenced more by its physiological status. Since the environmental exposure of Hg in Segara Anakan estuary was relatively high, pregnant women from this region should consider the potential hazard of Hg to their fetus when consuming aquatic organism of higher trophic level such as estuarine crabs.